Dealing with aging and multigeneration workforce topics at top global companies: evidence from public disclosure information - Castellucci, Hector Ignácio (2018)
The way organizations deal with aging employees and the way they manage the existence of a multigenerational gap within the workforce falls well within the scope some public information reporting practices, such as corporate responsibility. The aim of this study is to ascertain the level and characteristics of reporting practices on aging and multigenerational workforce among the top 50 global companies. The analysis of the public information disclosure was carried out using a quantitative approach by applying a three-stage data collection procedure. It can be concluded that companies' information disclosure about aging workforce topics is markedly low and, accordingly, it appears at a low level of relevancy on their institutional websites structure/content, as well as in their public reports. The main finding pointed out to the fact that top global companies do not widely report the way they take actions to deal with aging and multigenerational workforce challenges.